Prevalence of Lesions and oral mucosal normal variations in an elderly populationin Costa Rica = Prevalencia de lesiones y variaciones de lo normal en la mucosa oral en una población de adultos mayores de Costa Rica - Fernández Chaves, José Manuel 1979-
To establish the prevalence of oral mucosal lesions and normal variations in a population of older adults. This observational study was conducted from 2015 to 2016 and involved 156 participants from Los Guido (San José, Costa Rica). The participants' sociodemographic information, risk factors, comorbidity, and clinical examination were evaluated and analyzed descriptively and qualitatively. Findings in oral mucosa were found to preferentially affect women (n=111; 71%) and individuals between the ages of 60 and 69 years (n=65; 42%), having smoking as a risk factor (n=67; 43%), and suffering from arterial hypertension (n=101; 65%). Intraoral findings were mainly presented together with variations from normal and pathology (n=71; 46%), predominantly one variation from normal (n=67; 33%) and one pathology (n=51; 43%). The most prevalent normal variations were the saburral tongue, lingual varicose veins, and cryptic tonsils. Infectious diseases (n=33; 21%), potentially malignant disorders (n=30; 19%), and physical and chemical injuries (n=18; 12%) were the most prevalent groups. The four most predominant lesions were prosthetic stomatitis, actinic cheilitis, frictional keratosis, and atrophic glossitis. The differences in pathological groups were not statistically significant (p=0.392) when comparing the frequency ratio by sex. Variations of the normal anatomy are the predominant ones, the saburral tongue being the most prevalent individually; among the pathologies, the most remarkable group was the infectious diseases, and prosthetic stomatitis was the most frequent. The information about this subject in Costa Rica is limited. So it is important to conduct more studies that contribute to the oral health of the elderly population in this area.